Estimated fetal weight at mid‐gestation in prediction of pre‐eclampsia in singleton pregnancy. (2nd February 2022) - Frei, L.; Wright, A.; Syngelaki, A.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objective: To examine the distribution of birth weight according to gestational age in pregnancies complicated by pre‐eclampsia (PE) and assess the potential value of sonographic estimated fetal weight (EFW) at mid‐gestation as a predictor of PE. Methods: The data for this study were derived from prospective screening for adverse obstetric outcome in 93 911 women with a singleton pregnancy attending for routine pregnancy care at 19 + 0 to 24 + 6 weeks' gestation in two UK maternity hospitals. This visit included recording of maternal demographic characteristics and medical history, sonographic EFW and measurement of mean arterial pressure (MAP) and uterine artery pulsatility index (UtA‐PI). The distribution of birth weight of pregnancies with and those without PE was assessed. The competing‐risks model was used to estimate the individual, patient‐specific risk of delivery with PE at < 32 and < 37 weeks' gestation and at any gestational age. The areas under the receiver‐operating‐characteristics curves and detection rates (DRs) of delivery with PE, at a 10% false‐positive rate (FPR), were assessed for various combinations of maternal risk factors, EFW, MAP and UtA‐PI. McNemar's test was used to determine the significance of difference in DR at a 10% FPR between screening with vs without EFW. Results: The study population contained 2843 (3.0%) pregnancies that subsequently developed PE, including 148 (0.2%) that delivered with PE at < 32 weeks' gestation and 654 (0.7%) that delivered with PE at < 37 weeks. Birth weight was < 10 th percentile in 82% of pregnancies with PE delivering at < 32 weeks' gestation and this decreased to 21% of those with PE delivering at ≥ 37 weeks. In screening for delivery with PE at < 32 and < 37 weeks' gestation, the DR, at a 10% FPR, achieved by maternal risk factors (51% and 46%, respectively) was improved by addition of EFW (69% and 51%, respectively). Similarly, addition of EFW improved the performance of screening by a combination of maternal risk factors and MAP from 72% to 80% for PE < 32 weeks and from 57% to 60% for PE < 37 weeks. EFW did not improve the predictive performance of screening by a combination of maternal risk factors, MAP and UtA‐PI. Conclusions: In pregnancies complicated by preterm PE, a high proportion of neonates are small‐for‐gestational age, and sonographic EFW at mid‐gestation can improve the prediction of early and preterm PE provided by maternal risk factors and MAP but not the prediction provided by a combination of maternal risk factors, MAP and UtA‐PI. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.